Technology spillovers embodied in international trade: Intertemporal, regional and sectoral effects in a global CGE - Enrica De Cian; Ramiro Parrado (Fondazione Eni Enrico Mattei (FEEM), 2012)
This paper uses a dynamic CGE model to assess the intertemporal and spatial dimension of technology spillovers embodied in international trade within a climate and trade policy framework. Three are the main contributions of the study. First, to include endogenous factor-biased technical change based on trade flows in a CGE model, particularly for energy and capital. Second, to analyse the implications of specific spillovers embodied in trade of capital goods (machinery and equipment), and third, to highlight the implications of accounting for indirect effects induced by spillovers. We find that explicitly modelling trade spillovers reveals significant effects thanks to the transmission mechanisms underlying imports of capital commodities. We then assess the net contribution of modelling trade spillovers within three policy scenarios. The aggregated net effects of spillovers are rather small confirming findings from previous studies. However, there are important international and intersectoral redistribution effects due to technology transfers represented as embodied spillovers.
Keywords: C68; E27; O12; Q54; Q56; O33; 330; Computable General Equilibrium Models; Climate Change; Economic Growth; Technological Spillovers